The right to die : public controversy, private matter - Gay, Kathlyn (Brookfield, Conn. : Millbrook Press, 1993)
A discussion of the debate concerning the right-to-die issue, including past and present views on euthanasia, the controversial subject of assisted suicide, and the legal ramifications.
Includes bibliographical references (p. 118-124) and index.
Keywords: Right to die -- Moral and ethical aspects -- Juvenile literature; Euthanasia -- Moral and ethical aspects -- Juvenile literature; Assisted suicide -- Moral and ethical aspects -- Juvenile literature; Death -- Social aspects -- Juvenile literature; Suicide -- Moral and ethical aspects -- Juvenile literature